An Analysis of Recognition of Extended Compound Sentences - Sevim Güneş (Informascope, 2013)
The aim of this research study was to clarify whether recognizing extended compound sentences is a problem for first grade ELT students of Dicle University. This study also investigated the effect of remedial teaching on students' recognition of extended compound sentences and gender differences in terms of the recognition of extended compound sentences. The participants were 35 first grade ELT students of Dicle University. A pre-test of 30 questions was  answered by the participants and the same test was answered as the post-test after 2-weeks of remedial teaching.